Urban regeneration programming in Poland in the years 2014–2020 - Masierek, Edyta (European Spatial Research and Policy, 2021)
In 2015, the National Urban Policy, The Urban Regeneration Law, and the Guidelines regarding urban regeneration in operational programmes for the years 2014–2020 were adopted in Poland. These documents marked a new direction for developing and implementing these difficult processes. Simultaneously, communes received support which was supposed to help them plan urban regeneration properly on the basis of reliable diagnoses of the initial state, considering their endogenous features and potentials, with active participation of local communities. The aim of the article is to present the Polish approach to regeneration programming. Its background is the analysis of the definitions of urban regeneration which have functioned in Polish literature since the 1990s followed by a presentation of Western European stages of the evolution of this subject. The analysis offered in the article as well as the resulting conclusions show that the Polish approach to regeneration follows the integrated model prevalent in Europe. It fits the discussions between the academics and practitioners regarding the designation of degraded areas in cities, the principles of regeneration programming, and active involvement of different stakeholders in the aforementioned processes.